Phantom Euboians - Papadopoulos, John K. (Journal of Mediterranean Archaeology, 1998)
This paper critically examines interpretations of social and economic pre-eminence and ethnicity in the eastern and central Mediterranean in the EIA. More particularly, it challenges the conventional view of Aegean, especially Euboian, primacy in early maritime trade and colonial ventures. To focus on one particular group - whether Greek, Levantine or other - to the neglect of others, is to miss the broader Mediterranean perspective and to impose national and nationalistic concepts which shift according to scholarly notions. Against the backdrop of a less-centralized and growing world-system, in which fluid boundaries allow for mobility of people and ideas, communities throughout the Mediterranean were affected and drawn together in a variety of ways. The process of ’blending’ was more profound than merely combining two or more cultures. The only way to understand the complexities of multi-ethnic communities is to examine the entire cultural milieu and assemblage, not just certain aspects of the material record, and to recognize the interplay of ethnic, class, gender and other divisions.